2013
DOI: 10.1073/pnas.1308755110
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α is required for osteoclast activation by estrogen deficiency in postmenopausal osteoporosis

Abstract: In women, estrogen deficiency after menopause frequently accelerates osteoclastic bone resorption, leading to osteoporosis, the most common skeletal disorder. However, mechanisms underlying osteoporosis resulting from estrogen deficiency remain largely unknown. Here we show that in bone-resorbing osteoclasts, estrogendependent destabilization of hypoxia-inducible factor 1 alpha (HIF1α), which is unstable in the presence of oxygen, plays a pivotal role in promoting bone loss in estrogen-deficient conditions. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
160
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(165 citation statements)
references
References 25 publications
1
160
0
1
Order By: Relevance
“…A recent study has reported that HIF1α is a crucial factor in the activation of osteoclasts that promote bone resorption after menopausal estrogen insufficiency. Indeed, estrogens prevent HIF1α activation, leading to the suppression of osteoclast activity (Miyauchi et al 2013). Nuclear factor-κB (NF-κB), a transcription factor of inflammatory genes, induces muscle atrophy, along with the loss of slow-twitch fibers (Li et al 2008, Wang & Pessin 2013.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported that HIF1α is a crucial factor in the activation of osteoclasts that promote bone resorption after menopausal estrogen insufficiency. Indeed, estrogens prevent HIF1α activation, leading to the suppression of osteoclast activity (Miyauchi et al 2013). Nuclear factor-κB (NF-κB), a transcription factor of inflammatory genes, induces muscle atrophy, along with the loss of slow-twitch fibers (Li et al 2008, Wang & Pessin 2013.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of oestrogen levels is related to the development of postmenopausal osteoporosis in female populations 5, 21. This study simulates menopause by removing the ovaries in female C57BL/6 mice, resulting in postmenopausal osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, osteoclastogenesis appears to be accelerated by increasing volumes of culture medium and a concomitant increase in nutrients, including glucose (3,5). Glucose was the principal energy source required for bone degradation (29), and hypoxia-inducible factor 1 alpha was stabilized in osteoclasts, leading to osteoclast activation (30). This suggests that the differentiation of large multinuclear osteoclasts may be influenced by the glucose content, and also by low concentrations of oxygen in the medium (6,7).…”
Section: Discussionmentioning
confidence: 99%